2017
DOI: 10.1063/1.4991491
|View full text |Cite
|
Sign up to set email alerts
|

Local structure of amorphous Ag5In5Sb60Te30 and In3SbTe2 phase change materials revealed by X-ray photoelectron and Raman spectroscopic studies

Abstract: Reversible switching between highly resistive (binary “0”) amorphous phase and low resistive (binary “1”) crystalline phase of chalcogenide-based Phase Change Materials is accredited for the development of next generation high-speed, non-volatile, data storage applications. The doped Sb-Te based materials have shown enhanced electrical/optical properties, compared to Ge-Sb-Te family for high-speed memory devices. We report here the local atomic structure of as-deposited amorphous Ag5In5Sb60Te30 (AIST) and In3S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…[ 26,27 ] Moreover, the Raman peaks observed at 176 and 188 cm −1 correspond to atomic vibrations from InSb [ 26,28 ] bonds and the broad peak at 153 cm −1 represents the Raman mode of a‐Te atoms. [ 25,29 ] It was observed that there is a significant increase in the peak of the InSb vibrational mode that corresponds to the binary level 010 (Figure 3b). This demonstrates the evolution of its crystalline phase, [ 30 ] where a‐Te frequencies shifted to 147 cm −1 due to the crystallization of Te.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…[ 26,27 ] Moreover, the Raman peaks observed at 176 and 188 cm −1 correspond to atomic vibrations from InSb [ 26,28 ] bonds and the broad peak at 153 cm −1 represents the Raman mode of a‐Te atoms. [ 25,29 ] It was observed that there is a significant increase in the peak of the InSb vibrational mode that corresponds to the binary level 010 (Figure 3b). This demonstrates the evolution of its crystalline phase, [ 30 ] where a‐Te frequencies shifted to 147 cm −1 due to the crystallization of Te.…”
Section: Figurementioning
confidence: 99%
“…The diffused Sb atoms from the InSb vibrational mode could increase the peak intensity of InSbTe bonds along with a redshift in its vibrational frequency toward 155 cm −1 . Furthermore, the c‐Te bond with In resulted in evolution of the InTe [ 25 ] vibration mode at 138 cm −1 . Although we could observe the new InTe peak, there was a significant increase in the InSbTe vibration mode, which displays the evolution of its crystalline phase.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the vibration modes of initial multilevel states (from 0000 to 0100) exhibit a blueshift (from 0000 to 0100) and followed by a redshift in the higher levels (from 1000 to 1010). The initial blueshift is due to the enhancement of Ag-In-Te modes (from 0000 to 0100), whereas, at the higher level (from 1000 to 1010), there is a suppression of the Ag-In-Te modes 44,45 and enhancement in the Ag-Sb-Te modes, 44,45 which results in the redshift in the Raman spectra (please refer to Figure S3 in the Supporting Information). Further, the vibrational modes of the Raman spectra deconvoluted using the Gaussian functions for the binary levels 0000 and 1111 are shown in Figure S2a,b (Supporting Information), and the corresponding peak assignments of the fitting are listed in Table S3 (Supporting Information).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…35 Due to its high crystallization temperature, IST was also investigated for applications in PCMs which require data retention at temperature higher than those achievable with GST alloys. 28,[36][37][38][39][40][41][42] The crystal structure of cubic In 3 SbTe 2 along the pseudobinary InSb-InTe tie-line was assigned to the Fm 3m space group, with an experimental lattice constant of 6.126Å. 41 IST shares the rocksalt geometry of GeSbTe alloys in the metastable cubic phase with In atoms occupying the cationic sublattice and Sb and Te atoms randomly occupying the anionic sublattice, as shown by XRD and neutron diffraction experiments.…”
Section: Resultsmentioning
confidence: 99%